Depressed Adolescents' Pupillary Response to Peer Acceptance and Rejection: The Role of Rumination. - Stone, Lindsey; Silk, Jennifer; Siegle, Greg; Lee, Kyung; Stroud, Laura; Nelson, Eric; Dahl, Ronald; Jones, Neil; Stone, Lindsey B; Silk, Jennifer S; Siegle, Greg J; Lee, Kyung Hwa; et al. (Child Psychiatry & Human Development, 2016)
Heightened emotional reactivity to peer feedback is predictive of adolescents' depression risk. Examining variation in emotional reactivity within currently depressed adolescents may identify subgroups that struggle the most with these daily interactions. We tested whether trait rumination, which amplifies emotional reactions, explained variance in depressed adolescents' physiological reactivity to peer feedback, hypothesizing that rumination would be associated with greater pupillary response to peer rejection and diminished response to peer acceptance. Twenty currently depressed adolescents (12-17) completed a virtual peer interaction paradigm where they received fictitious rejection and acceptance feedback. Pupillary response provided a time-sensitive index of physiological arousal. Rumination was associated with greater initial pupil dilation to both peer rejection and acceptance, and diminished late pupillary response to peer acceptance trials only. Results indicate that depressed adolescents high on trait rumination are more reactive to social feedback regardless of valence, but fail to sustain cognitive-affective load on positive feedback.